Reduced thermal expansion and improved electrochemical performance in Pr-substituted SrFeO3 as symmetrical electrode for Solid Oxide Fuel Cells - Sánchez Caballero, Abraham; Zamudio-García, Javier; dos Santos-Gómez, Lucía; da Silva, Iván; Pérez-Coll, Domingo; Porras-Vázquez, José Manuel; Marrero-López, David (ACS Publications, 2025)
Advances in doping strategies have significantly improved the properties of SrFeO3-based electrodes. However, challenges such as high thermal expansion coefficients and limited redox stability remain critical issues that require further investigation. This study focuses on the optimization of (Sr1–xPrx)0.95FeO3–δ (0 < x ≤ 1) series, evaluating the effects of praseodymium content on thermal expansion, redox stability, and electrochemical performance for potential application as both air and fuel electrodes in symmetrical solid oxide fuel cells. Rietveld refinements of X-ray and neutron diffraction data reveal a phase transformation from tetragonal to cubic symmetry with Pr content (0.2 ≤ x ≤ 0.4), followed by a transition to orthorhombic symmetry (x ≥ 0.6). Thermogravimetric and dilatometric analyses demonstrate that higher Pr content effectively reduces both oxygen nonstoichiometry and the thermal expansion coefficients, which decrease from 31 × 10–6 K–1 for x = 0.2 to 8.4 × 10–6 K–1 for x = 1. Meanwhile the electrical conductivity remains relatively unaffected by the Pr-content up to x = 0.8, reaching values as high as 116 S cm–1 at 700 °C in air. Additionally, the electrode polarization resistances are relatively low across the series, e.g. 0.11 Ω cm2 in air and 0.09 Ω cm2 in H2 for x = 0.6 at 700 °C, while exhibiting excellent redox cycling stability. These findings indicate that (Sr1–xPrx)0.95FeO3–δ (x ≥ 0.6) materials are promising electrodes, offering tunable thermal expansion and electrochemical properties for reliable performance in both oxidizing and reducing environments.
Keywords: Electroquímica; Química atmosférica; Conductividad eléctrica; Electrodos; Oxígeno; Oxidorreducción; Expansión (Calor); Anoxia; Propiedades eléctricas; Atmospheric chemistry; Electrical conductivity; Electrodes; Oxygen; Redox reactions; Symmetrical solid oxide cell; SrFeO3; Thermal expansion; Oxygen deficiency; Electrical properties